Synaptic mechanisms underlying the elevated sympathetic outflow in fructose-induced hypertension - Zhu, Yun; Sun, Haiying; Wang, Hongjie; Li, Na (Frontiers in Physiology, 2024)
Metabolic syndrome is associated with cardiovascular dysfunction, including elevated sympathetic outflow. However, the underlying brain mechanisms are unclear. The nucleus tractus solitarius (NTS) critically regulates autonomic reflexes related to cardiovascular function and contains neurons projecting to the caudal ventrolateral medulla (CVLM). Nitric oxide (NO) is a diffusible free-radical messenger in the vascular, immune, and nervous systems. In this study, we determine if NO in the NTS is involved in the synaptic plasticity underlying the elevated sympathetic outflow in fructose-induced hypertension. We retrogradely labeled CVLM-projecting NTS neurons through the injection of FluoSpheres into the CVLM in a fructose-fed rat model to determine the cellular mechanism involved in increased sympathetic outflow. Fructose feeding increased the blood pressure and glucose levels, which represent metabolic syndrome. We found that fructose feeding reduces the NO precursor L-arginine-induced increase in the firing activity of CVLM-projecting NTS neurons. Furthermore, fructose feeding reduces the L-arginine-induced increase in presynaptic spontaneous glutamatergic synaptic inputs to NTS neurons, while NO donor DEA/NO produces an increase in glutamatergic synaptic inputs in fructose-fed rats similar to that in vehicle-treated rats. In addition, fructose feeding reduces the NO-induced depressor response and sympathoinhibition. These data suggested that fructose feeding reduced NO production and, thus, the subsequent NO-induced glutamate releases in the NTS and depressor response. The findings of this study provide new insights into the central mechanisms involved in the neural control of cardiovascular and autonomic functions in the NTS in metabolic syndrome.